ANALISA DAN PERANCANGAN JARINGAN WAN DENGAN SISCO GATEWAY LOAD BALANCING PROTOCOL (GLBP) MENGGUNAKAN SIMULATOR GNS3 - Hendi Suhendi; Miftah Fahmi; Ismail Saleh (Jurnal Computech & Bisnis (e-Journal), 2022)
Lines of communication cannot be separated from the various problems that can interfere with data traffic in it. One problem that arises is the rupture that caused the destruction of communication lines or fiber optic cable intermediary.With a high level of reliability demanded data on the company's lines of communication so that the need for technology that can provide solutions to problems in the network data communication lines. It is very necessary especially companies manage databases and the data is very important to maintain.The use of gateway load balancing technology (GLBP) of cisco is expected to provide data communications reliability in need in the company.Gateway Load Balancing Protocol is the technology division of the traffic load of data to each gateway router or a group who are members of the GLBP. This technology can also divert traffic data gateway router it is damaged or dies communication path to the gateway are functioning properly. GLBP is an improvement on previous technology hot standby routing protocol (HSRP) to provide load balancing functionality. Keywords: Load Balancing, GLBP, Cisco Router